Representasi Kesehatan Mental dan Pesan Moral dalam Komik “Beban di Balik Senyuman”: Kajian Semiotika - Mardiyah, Azimah; Azkiya, Haura; Salsabila, Naurah (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
The development of technology makes literary works have various forms, one of which is in the form of digital comics that can be accessed anywhere easily. This study analyzes a digital comic entitled "The Burden Behind a Smile" with a mental health theme uploaded on the @mokhsa.jiwa Instagram account. This research is a semiotic study that aims to find out the depiction of mental health and moral messages in the comic. The theory used is Charles Sanders Peirce's semiotic theory which examines signs in the form of icons, symbols, and indices. The results of the analysis state that mental health in the comic is mostly represented through the image of an empty glass filled with water as a depiction of the character's mind in the comic which continues to be filled with various burdens of thoughts and expectations of others. In addition, the expressions used by the characters also illustrate the mental health of the characters. The digital comic "The Burden Behind a Smile" contains a moral message in the form of the importance of maintaining mental health by prioritizing yourself and maintaining your emotions.